Analisa Rekayasa Nilai (Value Engineering) pada Struktur Bangunan SDN Karangketug 3 Kota Pasuruan - Anwar, Khoirul; Sasongko, Januar (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The construction project of SDN Karangketug 3 in Pasuruan City includes several high-cost components that could still be optimized through efficiency improvements. In the structural work, the researcher attempted to modify the structural design by exploring alternative design options without compromising the quality or strength of the structure, using Value Engineering techniques. The research process involved several stages: Observation, Design and Cost Identification, Structural Analysis, Cost Estimation, and Analysis Results. Cost savings were achieved by reducing the dimensions of the beam and column cross-sections, while ensuring structural strength was maintained using the SAP2000 software program, and recalculating the optimal budget. SAP2000 analysis showed that all alternative frames passed the stress/capacity check. The optimal budget after value engineering for the beam and column structure amounted to a 34.23% reduction, from the initial cost of Rp. 116,284,340.70 to Rp. 76,481,631.65, representing a saving of Rp. 39,802,709.05.